Demographic history influences spatial patterns of genetic diversityin recently expanded coyote (Canis latrans) populations. (March 2018) - Heppenheimer, Elizabeth; Cosio, Daniela; Brzeski, Kristin; Caudill, Danny; Van Why, Kyle; Chamberlain, Michael; Hinton, Joseph; vonHoldt, Bridgett
Abstract Human-mediated range expansions have increased in recent decades and represent unique opportunities to evaluate genetic outcomes of establishing peripheral populations across broad expansion fronts. Over the past century, coyotes (Canis latrans ) have undergone a pervasive range expansion and now inhabit every state in the continental United States. Coyote expansion into eastern North America was facilitated by anthropogenic landscape changes and followed two broad expansion fronts. The northern expansion extended through the Great Lakes region and southern Canada, where hybridization with remnant wolf populations was common. The southern and more recent expansion front occurred approximately 40 years later and across territory where gray wolves have been historically absent and remnant red wolves were extirpated in the 1970s. We conducted a genetic survey at 10 microsatellite loci of 482 coyotes originating from 11 eastern U.S. states to address how divergent demographic histories influence geographic patterns of genetic diversity. We found that population structure corresponded to a north–south divide, which is consistent with the two known expansion routes. Additionally, we observed extremely high genetic diversity, which is atypical of recently expanded populations and is likely the result of multiple complex demographic processes, in addition to hybridization with otherCanis species. Finally, we considered the transition of allele frequencies across geographic space and suggest the mid-Atlantic states of North Carolina and Virginia as an emerging contact zone between these two distinct coyote expansion fronts.